Comparison of 3-dimensional and 2-dimensional quantitative coronary analysis measuring intracoronary lengths in patients undergoing diagnostic coronary angiography - Legutko, Jacek; Rzeszutko, Lukasz; Partyka, Lukasz; Depukat, Rafał; Wojdyla, Marcin; Barycz, Grzegorz; Wizimirski, Marcin; Stefaniak, Justyna; Tijdens, Folkert; Bary, Lizet; Dubiel, Jacek S.; Dudek, Dariusz; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Aim : To determine if three-dimensional quantitative coronary angiographic analysis (3D QCA) provides an advantage over two-dimensional (2D QCA) by increasing accuracy and precision of length measurements through compensating for foreshortening inherent to 2D images. Material and methods : A total of 800 inter-marker length measurements were performed (8 per wire, 5-40 mm) with novel 3D software and standard 2D software and compared with the true lengths of the inter-marker distances on the wire in coronary vessels of 21 patients recruited. Results : 2D QCA generally underestimated true length in comparison to 3D, and the discrepancy increased with absolute length. In contrast, 3D QCA showed a minimal difference from true length over the examined range of lengths. Conclusions : 3D QCA minimizes errors in length measurements associated with foreshortening, shows minimal difference from true length, and performs significantly better in comparison to 2D QCA. The advantage of 3D QCA is more pronounced at longer lengths.